DINAMIKA PENDIDIKAN AGAMA ISLAM DALAM MERESPONS ARUS INFORMASI GLOBAL PADA REMAJA MUSLIM - Nadhifa Arufah Cafshah; Fatoni, Ilham; Muhammad Al Imron; Icha Mufassiroh Asy Syauqi; Choirul Anwar; Syaiful Anwar; Muhammad Ihsan Dacholfany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the dynamics of Islamic Religious Education (IRE) in responding to the global flow of information that affects the understanding and character of Muslim youth. The globalization of information has significantly changed how adolescents access religious knowledge, presenting challenges in internalizing moderate Islamic values. This research adopts a qualitative approach using library research methods. Data were collected from primary and secondary literature sources such as scientific journals, books, and official documents related to globalization and Islamic education. The analysis was conducted through a critical review of these sources to identify themes, patterns, and strategies relevant to Islamic education.The findings reveal that Muslim adolescents' religious understanding is highly influenced by digital content, especially through social medi a. The role of IRE teachers is crucial in guiding students to critically evaluate religious information and fostering reflective awareness of Islamic teachings. Effective strategies identified include the integration of local and global values, the use of educational technology, and the development of an adaptive and responsive curriculum. Islamic Religious Education must continuously innovate to produce a generation of Muslims who are critical thinkers, tolerant, and competitive in a globalized era.